Preparation and Application of Platinum Composite Microelectrode (PCM) for the Routine Analysis of Acetaminophen in Pharmaceutical Products - Riyanto Riyanto; Ahmad Safarudin (Indonesian Journal of Chemistry, 2014)
Preparation and application of platinum composite microelectrode (PCM) for the routine analysis of acetaminophen in pharmaceutical products has been carried out. This electrode was prepare by Pt powder and PVC in 4 mL tetrahydrofuran (THF) solvent and swirled flatly to homogeneous followed by drying in an oven at 100 °C for 3 h. The mixture was placed in 0.5 cm diameter stainless steel mould and pressed at 10 ton/cm2. The cyclic voltammetry were performed in a three electrodes system using PCM as a working electrode, an Ag/AgCl (saturated KCl) as reference electrode and platinum wire as the counter electrode. Electroanalysis of acetaminophen was performed in 0.1 M H2SO4 as an electrolyte. The result of the study showed that the correlation of determination using PCM electrode for electroanalysis acetaminophen was R2 = 0.999. Precision, recovery, LOD and LOQ of the PCM towards acetaminophen were found to be 1.04%, 100.54%, 19.52 mg/L and 65.08 mg/L, respectively. As a conclusion, the methods can be used for routine analysis of acetaminophen in pharmaceutical product. Simplicity of sample preparation and use of low cost reagents are the additional benefit of this method.